Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T19:42:54+01:00
A) 3(x + 1) = 2x
3x + 3 = 2x
3x - 2x = -3
x = -3

b) 5(z-2) = 7(1 - z)
5z - 10 = 7 - 7z
5z + 7z = 7 + 10
12z = 17 / :12
z = 17/12
z = 1 i 5/12

c) 2(x + 4) - 6 = 3(x - 2) + 7x
2x + 8 - 6 = 3x - 6 + 7x
2x + 2 = 10x - 6
2x - 10x = - 6 -2
-8x = -8 /: (-8)
x = 1
4 4 4
2010-03-23T19:44:23+01:00
A) 3(x + 1) = 2x
3x+3=2x
3x-2x=-3
x=-3
b) 5(z-2) = 7(1 - z)
5z-10=7-7z
5z+7z=7+10
12z=17 / :12
z=17/12
z= 1 i 5/12
c) 2(x + 4) - 6 = 3(x - 2) + 7x
2x+8-6=3x-6+7x
2x-3x-7x=-6+6-8
-8x=-8 / :(-8)
x=1
1 4 1
2010-03-23T19:45:00+01:00
A) 3(x + 1) = 2x
3x+3=2x
3x-2x=3
x=3
b) 5(z-2) = 7(1 - z)
5z-10=7-7z
-10-7=-5z-7z
-17=-13z/:-13
z=13/17-trzynaście siedemnastych
c) 2(x + 4) - 6 = 3(x - 2) + 7x
2x+8-6=3x-6+7x
2x-3x-7x=-8+6-6
-8x=-8/:-8
x=1
1 4 1